La contribución de Darwin al surgimiento de la psicología evolutiva (2011)
ABSTRACT: Evolutionary psychology may appear on the scene because which passes from a conception of permanent until such a conception of change, which generates large effects on the political, social and scientific fields. This transformation takes place in a historical process marked by the theory of evolution of Charles Darwin and is reinforced by other historical elements as the French Revolution and the theory of relativity in physics. For that, we transcended the immobility of Parmenides and we accepted the mutability of the being of Heraclitus, an event that is announced by Nietzsche as the death of God. This event can be understood as questioning the binomial God-truth, where truth no longer has a divine nature and, therefore, becomes a matter purely human and as fallible as a matter: the truth is no longer one eternal and unchangeable, and man, losing his divine attributes, becomes the object of study of science.